Development and testing of subsonic tandem deceleration system. (5th October 2016) - Samani, M.; Mahyari, M. Faraji
ABSTRACT: For many years, deceleration systems developed in an evolutionary fashion. This evolution needed flight test and experimental data. Concurrently, payload became much more expensive and needed to be safer. Today, there are a variety of methods employed to recover airborne bodies such as bio-capsules, reentry satellites, carrier missiles' boosters, reentry satellites, etc. Most of these methods make use of a parachute landing system in which recovery occurs in multiple phases. This paper studies the final phase of the subsonic recovery scenario for which a multi-phase deceleration system has been designed. To observe and evaluate system performance, a test projectile is designed that accelerates the payload to a certain velocity in order to test the recovery system. Finally, theoretical and test results are compared to indicate the appropriate design and reliable deceleration velocity in a space payload recovery.